2020
DOI: 10.1084/jem.20200050
|View full text |Cite
|
Sign up to set email alerts
|

Longevity and replenishment of human liver-resident memory T cells and mononuclear phagocytes

Abstract: The human liver contains specialized subsets of mononuclear phagocytes (MNPs) and T cells, but whether these have definitive features of tissue residence (long-term retention, lack of egress) and/or can be replenished from the circulation remains unclear. Here we addressed these questions using HLA-mismatched liver allografts to discriminate the liver-resident (donor) from the infiltrating (recipient) immune composition. Allografts were rapidly infiltrated by recipient leukocytes, which recapitulated the liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
95
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 42 publications
7
95
1
Order By: Relevance
“…As mentioned earlier, contrary to liver T RM cells in mice which express high levels of Hobit and low to intermediate levels of Blimp1 [73], human liver T RM cells are Hobit low Blimp1 high [58]. In a recent publication, a small proportion of donor cells were found in HLA-mismatched liver and allografts 11 years after transplant, demonstrating the resident nature and remarkable longevity of these cells [104].…”
Section: Identification Of Liver Trm Cellsmentioning
confidence: 81%
“…As mentioned earlier, contrary to liver T RM cells in mice which express high levels of Hobit and low to intermediate levels of Blimp1 [73], human liver T RM cells are Hobit low Blimp1 high [58]. In a recent publication, a small proportion of donor cells were found in HLA-mismatched liver and allografts 11 years after transplant, demonstrating the resident nature and remarkable longevity of these cells [104].…”
Section: Identification Of Liver Trm Cellsmentioning
confidence: 81%
“…The CD69+CD103− subpopulation is proposed to be a subpopulation that can recirculate and take on other functions upon pathogen challenge, whereas the CD69+CD103+ are defined to be truly liver resident [ 9 ]. In contrast, it could be shown that the majority of CD4+ T RM cells are long living and tissue-resident cells that express high levels of CD69 and show a low CD103 expression [ 10 ].…”
Section: Phenotype and Development Of T Rm Cellmentioning
confidence: 99%
“…Additionally, they showed that recipient CD8+ and CD4+ T cells could develop a T RM phenotype although the recipient-derived T RM cells tended to express fewer liver-resident markers. Furthermore, a small population of donor-derived CD4+ T RM cells was detectable [ 10 ]. To conclude, there are strong indications that liver T RM cells can develop from two different origins ( Figure 2 ).…”
Section: Phenotype and Development Of T Rm Cellmentioning
confidence: 99%
See 2 more Smart Citations